2018
DOI: 10.1016/j.biocel.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

MAPK p38 regulates inflammatory gene expression via tristetraprolin: Doing good by stealth

Abstract: Tristetraprolin (TTP) is an RNA-destabilizing protein that exerts profound anti-inflammatory effects by inhibiting the expression of tumour necrosis factor and many other inflammatory mediators. The mitogen-activated protein kinase (MAPK) p38 signaling pathway controls the strength and duration of inflammatory responses by regulating both the expression and function of TTP. The kinase MK2 (MAPK activated kinase 2) is activated by MAPK p38, and in turn phosphorylates TTP at two critical serine residues. One con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
(88 reference statements)
3
41
0
Order By: Relevance
“…Indeed c-di-AMP turned out to be capable of activating the p38 MAPK, which includes the phosphorylation of p38 and induction and phosphorylation of TTP. Overall this activation is similar to that of LPS (41), albeit with at least one significant difference. The phosphorylation of p38 by LPS is transient, peaks at 30 min, and returns to near-background levels after only 1 h (42), whereas the p38 phosphorylation by c-di-AMP is slower and sustained; it starts early after treatment and continues to be strongly phosphorylated even after 4 h. This is in agreement with the effect of c-di-AMP on the expression of ARE-containing nLuc reporter which was more significant at 8 h post-treatment compared to earlier time points.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed c-di-AMP turned out to be capable of activating the p38 MAPK, which includes the phosphorylation of p38 and induction and phosphorylation of TTP. Overall this activation is similar to that of LPS (41), albeit with at least one significant difference. The phosphorylation of p38 by LPS is transient, peaks at 30 min, and returns to near-background levels after only 1 h (42), whereas the p38 phosphorylation by c-di-AMP is slower and sustained; it starts early after treatment and continues to be strongly phosphorylated even after 4 h. This is in agreement with the effect of c-di-AMP on the expression of ARE-containing nLuc reporter which was more significant at 8 h post-treatment compared to earlier time points.…”
Section: Discussionsupporting
confidence: 67%
“…When ectopic expression of TTP S316A or TTP S316D in TTO KO cells, the decrease at 1 h was not recovered (Fig.5C). We suggest that the dynamic TTP phosphorylation is required for the bi-phasic TNFα expression [50,51], and the lower amount and hypo-phosphorylated TTP at 1 h induction (Fig.4A) exhibits higher mRNA destabilization activity. Like phosphorylation at serines 52 and 178 by p38-MK2 [27], Ser316 phosphorylation of TTP also displayed cytoplasmic localization (Fig.6C).…”
Section: Discussionmentioning
confidence: 88%
“…Some studies suggested that the RNA degradation activity of TTP is negatively regulated by p38 MAPK-dependent signaling (Stoecklin et al, 2004;Brook et al, 2006;Hitti et al, 2006). However, the impact of the p38 pathway on TTP expression and function remains controversial (O'Neil et al, 2018). TTP is found at sites of inflammation, and is colocalized with active p38 MAPK (Ross et al, 2017).…”
Section: Discussionmentioning
confidence: 99%